Pembentukan Karakter Muslim Melalui Pendidikan Indigenous Di Indonesia - Salahuddin Abdul Rahman (Universitas Muhammadiyah Jember, 2021)
The character of the Republic of Indonesia is clearly expressed in each point of Pancasila (the Five Principles) which constitutes the basis for the nation. More recently, this character has been eroded by the effects of globalization, that cannot be avoided, the easy access to information today is one of the factors behind the deterioration of the nation's moral character. So, there are needs to be a filter in character formation. The author of the study used library research in the writing of articles. The author used books as data sources. Library research, commonly called library research, does so by studying written sources. The nature of this research is descriptive. Research subject in this article from secondary data. And the result of this study is that indigenous Indonesia education, which was instilled by ancestors, has long been a model of boarding school, primarily forming a true Muslim character. So, when associated with the current situation of declining character or morality of the children of nations, it is appropriate to look back in time, in an effort to correct the misconceptions of education that we are currently pursuing.